The study on the awareness towards social security among employees in Tesco Peringgit Melaka / Mohd Shazmie Ishak and Muhd Fazril Muammar Gadaffi Jasni - Ishak, Mohd Shazmie; Jasni, Muhd Fazril Muammar Gadaffi (Faculty of Administrative Science and Policy Studies, 2012)
Nowadays there are a lots of employment injury at workplace. Social Security Organisation (SOCSO) is one of the organisations that provide protection for workers against the contingencies of employment injury including commuting accidents and occupational diseases as well as invalidity and death. Malaysian workforces are increasing and more jobs are offered to the society especially in private sector. More risk and diseases in workplace also face by the employee as the work become more complex and need to well prepare for any consequences either as a result of work or social cycle. Social security protection plays an important role in providing protection and assurance to employees. Having awareness employees is the main factor for an organisation to achieve success and the main purpose for the social security of its existence is to serve employee interest and awareness of social security among their employees. However, to increase the awareness among the employee is not an easy task because being a construct in psychology, awareness is influence by many factors. At many instances organisation strategies activities is to boost their employees performance. Moreover, these activities do not give many benefits mainly due to the lack of proper follow up. The employees don’t truly know about the flows of SOCSO’s claimed process. In order to determine awareness, we had conducted the research and a tool used was questionnaire. 112 questionnaires was distributed and the feedback showed that the factors that influencing the awareness was employees satisfaction, management support and employees attitude.